Studying mitigating factors of the framing effect: a survey of Brazilian university students - Santos, Filipe Ferreira dos; Silva, Daniel Jose Cardoso da (Seven Editora, 2023)
This research sought to identify whether factors such as age, level of Education, and Religiosity could influence the behavior of people regarding decision-making in situations where there is exposure to financial risk. The study has as its theoretical foundation the prospect theory, proposed by Kahneman and Tversky (1979), and seeks to understand the influence of the framing effect in the decision process. The sample included observations from all political regions of the country and had the participation of 423 students distributed among undergraduate courses in Business Administration, Accounting, and Economics. As an instrument of data collection, a questionnaire was applied to the students to get to know their profile, in addition to submitting them to problem questions to assess whether their behavior would be affected by the presence of financial risk in their investments. Based on the answers sent by the respondents and using Logit regressions, the results show that the variable age did not present, in any of the constructed scenarios, statistical significance to explain the rationality (or lack of it) of the choices. The results also suggest that there is no accuracy in the claim that Education can be considered a mitigating driver of the framing effect. Finally, the results indicate that only Religiosity, among the factors analyzed here, can statistically significantly influence the behavior of respondents, being considered a mitigating driver of the effects of the prospect theory, including its framing effect. DOI:https://doi.org/10.56238/alookdevelopv1-045